Viral discourse - Jones, Rodney H. 1959- (Cambridge University Press, 2021)
This Element consists of ten short pieces written by prominent discourse analysts in the midst of the COVID-19 pandemic. Each piece focuses on a different aspect of the pandemic, from the debate over wearing face masks to the metaphors used by politicians and journalists in different countries to talk about the virus. Each of the pieces also makes use of a different approach to analysing discourse (e.g. Critical Discourse Analysis, Genre Analysis, Corpus Assisted Discourse Analysis) and demonstrates how that approach can be applied to a small set of data. The aim of the Element is to show how the range of tools available to discourse analysts can be brought to bear on a pressing, 'real-world' problem, and how discourse analysis can contribute to formulating 'real-world' solutions to the problem